Swedish ABSAbank - Språkbanken Text (University of Gothenburg, 2024)
An annotated Swedish corpus for aspect-based sentiment analysis

Svensk annoterad korpus för aspektbaserad attitydanalys
Svensk ABSAbank
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik